Semi-automatic of steer by wire system using fuzzy logic control and swarm optimization - Fachrudin Hunaini; Dicky Dikananda Nafis; Purbo Suwandono; Gatot Subiyakto (Institute of Advanced Engineering and Science, 2023)
The semi-automatic steer by wire system is a vehicle steering system that does not use a mechanical link but uses an electric drive, so that the steer wheel is equipped with an angle sensor as a control system input to adjust the electric drive rotation when determining the direction of the front wheels of the vehicle. The control system uses fuzzy logic control (FLC) is optimized using swarm-based optimization. Performance testing of the optimal control system is carried out using Software in the loop simulations and hardware in the loop simulations which were then applied to the steering system prototype equipped with rack-pinion and wheel steer. The test results show that the optimal control system performance reaches a C-RMS error of 6.712. The prototype that was built has two kinds of ratios between the steering angle and the vehicle wheel angle, namely a ratio of 1:6.25 for speeds below 10 km/h making it suitable for operation when the vehicle is maneuvering in the parking area and a ratio of 1:25 for speeds above 10 km/h which is suitable for operation when the vehicle is traveling at medium or high speed.